2013
DOI: 10.1007/s40489-013-0005-2
|View full text |Cite
|
Sign up to set email alerts
|

The Most Commonly Reported Behavior Analytic Methods in Early Intensive Autism Treatments

Abstract: Early intensive behavioral interventions have become a very popular treatment in the field of autism spectrum disorders. Given the rapidly expanding use of these methods and the amount of money and resources being devoted to these programs, analyses of these practices is warranted. This paper looks at treatment studies on the topic. The children treated were largely diagnosed with pervasive developmental disorder not otherwise specified or autism diagnoses. One-to-one training was typical as were structured cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…While these exclusion criteria are set to create homogeneous samples for research purposes, they reduce generalizability to those who are seen in clinical and community-based settings, providing little information about which programs should be recommended based on different pre-treatment characteristics in the wider ASD population. Children with medical conditions, seizures, and/or severe intellectual disability make up a significant proportion of the ASD population ( 65 , 66 ), and they are more likely to be referred to treatment programs compared to children with no identifiable comorbid features ( 67 , 68 ). Therefore, research on their responses to different programs is crucial to inform clinical practice, so that enrollment to an intervention service is most likely to offer benefits and cause no harm.…”
Section: Limitations With Current Approaches To Research On Predictormentioning
confidence: 99%
“…While these exclusion criteria are set to create homogeneous samples for research purposes, they reduce generalizability to those who are seen in clinical and community-based settings, providing little information about which programs should be recommended based on different pre-treatment characteristics in the wider ASD population. Children with medical conditions, seizures, and/or severe intellectual disability make up a significant proportion of the ASD population ( 65 , 66 ), and they are more likely to be referred to treatment programs compared to children with no identifiable comorbid features ( 67 , 68 ). Therefore, research on their responses to different programs is crucial to inform clinical practice, so that enrollment to an intervention service is most likely to offer benefits and cause no harm.…”
Section: Limitations With Current Approaches To Research On Predictormentioning
confidence: 99%
“…Perhaps more striking is that only 2 of the 19 could be classified as having excellent clinical impact. Interestingly, both these studies demonstrated a very high efficiency as well.Group Size A 1:1 child-to-provider ratio was implemented for at least some proportion of the intervention for nearly all studies, consistent with the recent review by Matson and Jang (2014). In one study, behavioral intervention was provided to children in large groups only and, notably, one study did not indicate group size.…”
mentioning
confidence: 53%
“…EIBI is considered the gold standard treatment for individuals with ASD and is supported by a well-established body of literature (Eldevik et al, 2012;LeBlanc & Gillis, 2012;Matson & Jang, 2014;Peters-Scheffer et al, 2011). When delivered properly, EIBI can produce favorable outcomes for many individuals with ASD, including increased adaptive and daily living skills, full integration into mainstream classrooms, less engagement in stereotyped behaviors, and decreased problem behavior (LeBlanc & Gillis, 2012).…”
Section: Introductionmentioning
confidence: 99%